2017
DOI: 10.1111/aen.12312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wetland hydroperiod length on the functional structure of assemblages of Odonata

Abstract: The role of hydroperiod as an environmental filter in structuring wetland assemblages is usually associated with trait selection in invertebrates. However, the effects of changes in the hydroperiod of non-permanent wetlands on invertebrate assemblages are still unclear, and few studies have assessed the functional structure of insect assemblages along the hydroperiod gradient. In this study, we investigated the effects of different hydroperiod lengths on the functional structure of Odonata assemblages in non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In relation to the categories of hydroperiod length, we monitored the surface flooding areas of each wetland over two full hydrological cycles. Monthly surveys were carried out from September 2011 to September 2013 (Bieger, 2015;Boelter et al, 2018;Knauth et al, 2018;Pires et al, 2017Pires et al, , 2019Stenert et al, 2017). We used as classification criteria the length of the wet phase, the number of drought events, and the surface flooding area of each wetland over the monitoring period.…”
Section: Sampling Designmentioning
confidence: 99%
“…In relation to the categories of hydroperiod length, we monitored the surface flooding areas of each wetland over two full hydrological cycles. Monthly surveys were carried out from September 2011 to September 2013 (Bieger, 2015;Boelter et al, 2018;Knauth et al, 2018;Pires et al, 2017Pires et al, , 2019Stenert et al, 2017). We used as classification criteria the length of the wet phase, the number of drought events, and the surface flooding area of each wetland over the monitoring period.…”
Section: Sampling Designmentioning
confidence: 99%
“…), which occurs in ponds isolated from perennial water bodies usually alone or with coexisting non‐annual fish species in reduced abundance. In this region, ponds have a short hydroperiod and may face two flood cycles in the same year (Knauth et al ., 2019; Pires et al ., 2019). The coexisting non‐annual fish species contain potential predators ( e.g., Hoplias spp.)…”
Section: Introductionmentioning
confidence: 99%
“…As few studies have elucidated the role of competition in structuring odonate communities, the competition between closely related species would be expected to be more intense and likely to cause habitat segregation (Pires et al . 2017; Cerini et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although the deterministic theory on the distribution of species in the community prevails in community ecology (Grant 1972;Diamond 1975;Stone & Roberts 1990), many papers have shown that well-defined distribution patterns are absent in many communities (Volkov et al 2003;McGill et al 2006). As few studies have elucidated the role of competition in structuring odonate communities, the competition between closely related species would be expected to be more intense and likely to cause habitat segregation (Pires et al 2017;Cerini et al 2019).…”
Section: Species Co-occurrencementioning
confidence: 99%